Strong majorization uncertainty relations and experimental verifications - Yuan, Yuan (2023)
In spite of enormous theoretical and experimental progress in quantum uncertainty relations, the experimental investigation of the most current, and universal formalism of uncertainty relations, namely majorization uncertainty relations (MURs), has not been implemented yet. A major problem is that previous studies of majorization uncertainty relations mainly focus on their mathematical expressions, leaving the physical interpretation of these different forms unexplored. To address this problem, we employ a guessing game formalism to reveal physical differences between diverse forms of majorization uncertainty relations. Furthermore, we tighter the bounds of MURs by using flatness processes. Finally, we experimentally verify strong MURs in the photonic system to benchmark our theoretical results.